O estoicismo no pensamento de Luísa Sigea: a diotomia entre vida pùblica e vida privada - Santos, Maria Teresa (EDUEM, 2017)
O presente texto pretende analisar o modo como Sigea se posiciona em face da questão prática de viver na corte, tópico central do Colloquium (Dialogue de deux jeunes filles sur la vie de cour et la vie de retraite), publicado em Lisboa no ano de 1552. O texto desenvolve-se através da explicitação de alguns aspectos como os do humanismo renascentista português, para depois analisar o modo como Sigea interpreta a formação necessária para se alcançar a vida feliz (beata uita). This paper aims to examine Sigea’s position to the question of life at court, the central topic of the Colloquium (Dialogue between two young women on courtly and private life), published in 1552 in Lisbon. The development of the text starts with the explanation of some aspects such as the princes’ mirror (specula principum) and the palace circle of the Princess D. Maria, during the Portuguese Renaissance Humanism. Further on the text, it is analyzed how Sigea interprets the training needed to achieve happy life (beata uita).
Keywords: Sigea; estoicismo; espelhos de príncipes; beata uita